Molecular hijacking of siroheme for the synthesis of heme and d1 heme. - Bali, S; Lawrence, A; Lobo, SA; Saraiva, L; Golding, B; Palmer, D; Howard, M; Ferguson, S; Warren, M (2011)
Modified tetrapyrroles such as chlorophyll, heme, siroheme, vitamin B(12), coenzyme F(430), and heme d(1) underpin a wide range of essential biological functions in all domains of life, and it is therefore surprising that the syntheses of many of these life pigments remain poorly understood. It is known that the construction of the central molecular framework of modified tetrapyrroles is mediated via a common, core pathway. Herein a further branch of the modified tetrapyrrole biosynthesis pathway is described in denitrifying and sulfate-reducing bacteria as well as the Archaea. This process entails the hijacking of siroheme, the prosthetic group of sulfite and nitrite reductase, and its processing into heme and d(1) heme. The initial step in these transformations involves the decarboxylation of siroheme to give didecarboxysiroheme. For d(1) heme synthesis this intermediate has to undergo the replacement of two propionate side chains with oxygen functionalities and the introduction of a double bond into a further peripheral side chain. For heme synthesis didecarboxysiroheme is converted into Fe-coproporphyrin by oxidative loss of two acetic acid side chains. Fe-coproporphyrin is then transformed into heme by the oxidative decarboxylation of two propionate side chains. The mechanisms of these reactions are discussed and the evolutionary significance of another role for siroheme is examined.